How Do Gymnastics Coaches Provide Movement Feedback in Training?. Issue 6 (December 2015) - Jeraj, Damian; Veit, Juliane; Heinen, Thomas; Raab, Markus
The augmented feedback athletes receive from their coach is essential to improve performance. The aim of this exploratory study was to identify how coaches consider six feedback factors which might have an influence on the error-correction process. The six feedback factors were developed from a heuristic model of error correction, namely: a) visual perspective, b) visual experience, c) motor experience, d) personal relationship between coach and athlete, e) methodological knowledge, and f) biomechanical knowledge. Seventy-three active gymnastics coaches were asked to rank the importance and frequency of use of these six factors. In addition, we examined, in an exploratory way, if moderators can partly explain the weightings. Results show that the feedback factors can be ranked in importance and frequency of use, with methodological knowledge being the most essential in an error-correction situation. More studies are needed that explore if coaches should guide feedback according to their own motor experience. Gaze training for coaches is needed to improve the feedback and, ultimately, the movements.